2019
DOI: 10.1038/s41598-019-40302-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of phase structure evolution induced by alloying elements in Ti alloys via a chemical-short-range-order cluster model

Abstract: The prominent comprehensive properties of solid-solution- and intermetallic-based Ti alloys are derived from their diverse microstructures induced by multi-component alloying, which results in a chemical composition complexity. A cluster-plus-glue-atom model, characterizing the chemical short-range orders, was introduced to explore the relationships among the local atomic distributions of alloying elements in different phase structures of Ti alloys, including α -Ti, β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…In our previous alloys, we applied the cluster-formula approach into other compositionally complex systems to explore the relationship between the alloy composition and properties 37,64 . For instance, it is found that the compositions of Ni-base single crystal superalloys with prominent creep resistance satisfy a uniform cluster formula of ½Al À Ni 12 ðAl 1:5 Cr 1:5 Þ, in which all the alloying elements are classified into three groups, Al series (Al), Cr series (Cr), and Ni series (Ni) 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous alloys, we applied the cluster-formula approach into other compositionally complex systems to explore the relationship between the alloy composition and properties 37,64 . For instance, it is found that the compositions of Ni-base single crystal superalloys with prominent creep resistance satisfy a uniform cluster formula of ½Al À Ni 12 ðAl 1:5 Cr 1:5 Þ, in which all the alloying elements are classified into three groups, Al series (Al), Cr series (Cr), and Ni series (Ni) 65 .…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the cluster is the nearest-neighbor polyhedron centered by a solute atom that has strong interaction (characterized by a large negative enthalpy of mixing (ΔH) 36 ) with the base solvent atoms to represent the strongest CSRO. Some other solute atoms having weak interactions with the base (a positive ΔH) are certainly required to fill the space among clusters for the balance of atomic-packing density, named as glue atoms 37 . Thus, an uniform composition formula [cluster](glue atom) m (m being the glue-atom number) can be abstracted from this model, which is called the cluster-formula approach 18,19 .…”
Section: Characteristic Parameters In Low-e β-Ti Alloysmentioning
confidence: 99%
“…At room temperature, TiAl intermetallic alloys comprise of three major phases of intermetallics, namely; α 2 -Ti 3 Al (D0 19 structure), γ-TiAl (L1 0 structure) and β o -TiAl (B2 structure) [ 1 , 4 , 7 , 18 , 20 , 26 , 27 , 28 , 29 ]. The γ-TiAl phase has L1 0 tetragonal structure while α 2 -Ti 3 Al phase has a D0 19 hexagonal structure [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The α 2 -Ti 3 Al phase has an ordered hexagonal closed packed (HCP) structure [ 33 , 34 ] formed between 22 to 39 at.% Al content and transforms to an ordered structure from the disordered one at about 1180 °C with lattice parameters, a = 0.5782 nm and c = 0.4629 nm [ 14 , 34 ]. It is known to exhibit extremely poor toughness and tensile ductility at ambient temperatures while possessing good oxidation resistance and excellent elevated temperature specific strength [ 28 ]. Typical TiAl-based alloy microstructures consist of alternating α 2 /γ lamellae formed within the α-phase region and present a reciprocating crystallographic relationship of (0001)-α 2 || (111)-γ and <1120>-α 2 || <110>-γ [ 34 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation